Speech of Body Shaming, Insult and Defamation in Social Media in the Jurisdiction - Charles Butar-butar; Mhd Isman (Randwick International of Social Science Journal, 2023)
The purpose of this study is to analyze the pragmatic power of insulting and defamatory statements. Research is conducted using descriptive and qualitative methods. The information for this study comes from insulting and defamatory statements that were allegedly made by people who violated Articles 45 and 27 of Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 Concerning Information and Electronic Transactions that are Inrah or Have Legal Effect. The illocutionary speech act theory developed by Searle was the basis for this study. Data delivery techniques utilizing prosperous sampling. This indicates that the linguistic data used in the research is being used in the police investigation report (BAP). The distribution approach and the matching method were both employed in data analysis. The findings revealed a variety of illocutionary speech acts, including self-classification of weight in the form of mockery and censure, as well as appearance appraisal, appearance orientation, the satisfaction of body areas, and overweight obsession.